Ceruminous cystomatosis in a persian cat: case report - Lopes, Wesley Renosto; Garcia, Cinthia; Meira, Júlia [UNESP]; Odorcick, Bianca Maria; Ampese, Aila; Suder, Amanda; de Oliveira, Eduardo Conceição (Medicina Veterinaria (UFRPE), 2022)
Ceruminous cystomatosis is a non-neoplastic, benign condition of unknown etiology and characterized by dilatation and hyperplasia of ceruminous glands. It presents as multiple lesions with a nodular and/or vesicular appearance, located on the surface of the auricular pavilion and may extend to the region of the external acoustic meatus. The objective of this article is to report the clinical case of a 13-year-old female Persian feline with a history of chronic otitis. The animal had multiple nodules with a cystic characteristic and violet blue color, firm with a smooth surface, bilateral in the auricular pavilion. After the histopathological examination, the definitive diagnosis of feline ceruminous cystomatosis was reached and was opted for the surgery of complete excision of the auricular nodules, providing the clinical improvement of the patient.
Cistomatose ceruminosa em felino Persa: relato de caso
Keywords: auricle; hyperplasia; otitis